Inspired by Malacca Sultanate Palace / Nur Aina Anuar - Anuar, Nur Aina (2022)
The Malacca Sultanate Palace or Istana Kesultanan Melaka, is a museum housed in a reconstruction of the purported palace during the Malacca Sultanate. The palace museum measures 240 feet by 40 feet. It showcases a collection of some 1,350 items chronicling the history and culture of the Malacca Sultanate as well as the various communities that settled in Malacca during the sultanate period.